Islamic Resilience Based on Zakat: Integrating CIBEST–MPI to Assess the Multi-Dimensional Recovery in Post-Disaster - Undriani Undriani; Uswatun Hasanah; Nur Syamsu; Syaifullah M.S; Dede Arseyani Permatasari (TSAQAFAH, 2026)
Post-disaster recovery in Muslim-majority regions often faces distinctive obstacles because conventional assistance can overlook the spiritual and social resources that shape coping strategies and collective action. Islamic Social Finance (ISF)—especially zakat institutions—has therefore become an increasingly important recovery actor, yet robust evidence on sustained, long-term outcomes remains limited. This study assesses the effectiveness of the BAZNAS Sejahtera program in Palu, Indonesia, six years after the 2018 tsunami. It employs an integrated analytical framework that combines the CIBEST model of Islamic welfare, the Multidimensional Poverty Index (MPI), and disaster-recovery principles to examine changes in material and spiritual well-being, multidimensional deprivations, resilience, and the relationships among these domains. A qualitative case study was conducted with 16 beneficiaries across 11 sub-districts using structured questionnaires, semi-structured interviews, participant observation, and document analysis. The results show notable progress: income increased by 34.7%, assets by 68.75%, and zakat participation rose from 0% to 87.5%. Access to clean water reached 100%, while sanitation improved to 93.75%. Resilience strengthened across economic recovery (87.5%), social trust and networks, physical housing and infrastructure, and risk reduction (100% awareness; 75% preparedness). Importantly, the findings suggest reciprocity: stronger īmān, worship discipline, and trust-based ethics reinforced cohesion and livelihoods, while improved livelihoods enabled religious obligations—especially zakat—supporting transitions from mustahiq to muzakki (87.5%).